Comparative study of numerical methods used in prediction of post-crack behavior of waffle slabs (Journal of Civil Engineering Researchers, 2022)
One effective way to reduce dead and earthquake loads is to use waffle slabs. The use of waffle slabs leads to smaller sections. There are various methods for predicting the behavior of slabs, the most important of which is fracture mechanics. Considering the variety of geometry of waffle slabs, it is important to investigate the formation and growth of cracks in them. The current research aims to analyze the post-crack behavior of waffle slabs under common loading conditions using the finite element method by using numerical modeling to analyze cracks in reinforced concrete members. by comparing the obtained results with the laboratory sample, the optimal numerical model for predicting the behavior of the hollow slab was determined. The waffle slab sample was modeled with two types of distributed and concentrated loading conditions and two types of simple and fixed support conditions. The models were modeled by two methods of concrete damage plasticity and smeared cracked concrete by Abaqus software. Various parameters of these samples, including the load-displacement diagram, the load coincident with the formation of cracks, the displacement in the middle of the slab opening, and the pattern of the formation and propagation of cracks, etc., were discussed and investigated. To validate and control the modeling process, the laboratory results of the research of Nithyambigai G et al. in 2021 have been used. The outcomes of this study showed; a relatively good correspondence between the two methods of Concrete damage plasticity and the concrete smeared crack model, but due to the definition of failure in the Concrete damage plasticity method, more accurate results can be obtained.
Keywords: CDP Numerical Method; Crack Growth; Reinforced Concrete Slab; Concrete Smeared Cracking Method; waffle Slab